The pH sensor for flavivirus membrane fusion - Harrison, Stephen C. (The Rockefeller University Press, 2008)
Viruses that infect cells by uptake through endosomes have generally evolved to “sense” the local pH as part of the mechanism by which they penetrate into the cytosol. Even for the very well studied fusion proteins of enveloped viruses, identification of the specific pH sensor has been a challenge, one that has now been met successfully, for flaviviruses, by Fritz et al. (Fritz, R., K. Stiasny, and F.X. Heinz. 2008. J. Cell Biol. 183:353–361) in this issue. Thorough mutational analysis of conserved histidine residues in the envelope protein of tick-borne encephalitis virus led Fritz et al. (2008) to identify a histidine at a key domain interface as the critical pH sensor; its protonation triggers the large-scale conformational rearrangement that induces fusion of viral and endosomal membranes.